Jamnagar Petrochemical Complex - Reliance Industries Limited (2023)
A view of the Jamnagar Petrochemical Complex, the world's largest refining hub, built under the leadership of Shri Mukesh Ambani. It is currently ranked as one of the world's largest refining hubs.